Efficacy of entomopathogenic nematodes and fungi as biological control agents of woolly apple aphid, Eriosoma lanigerum (Hausmann) (Hemiptera: Aphididae) under South African conditions - Stokwe, Nomakholwa Faith (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.